Gas flaring reduction in the Indonesian oil and gas sector: Technical and economic potential of Clean Development Mechanism (CDM) projects - Gustya Indriani (Hamburg Institute of International Economics (HWWA), 2005)
Indonesia currently ranks as the world's 17th oil and 6th gas producer, but its production levels are slowly declining. In Indonesia, the oil companies may extract, process and market associated gas jointly with the State Oil and Gas Board. In addition, they are allowed to use associated gas in operations, as well as re-inject or flare gas that cannot be marketed. However, associated gas is still considered as a by-product of oil, which can disturb the oil flow. Due to the lack of markets, institutions and regulations, the associated gas is often simply flared instead of being used. Flaring currently amounts to about 5% of gas production and generates 10 million t CO2. On the company level, gas flaring data show that 80% of total GHG emission from flaring was released by ten companies. By using the Clean Development Mechanism (CDM) to reduce gas flaring, the economic use of gas will be maximised. Other options are gas re-injection, gas to pipeline, improvement of flare efficiency, Natural Gas Liquids recovery, GTL and fuel switch. Large scale projects in gas flaring reduction are more feasible, especially for remote oil fields. But some cases show that small scale projects in small fields with local market opportunity are feasible as well.
Keywords: 330